Advances in geo-spatial information science - Shi, Wenzhong (CRC Press, 2012)
"Covering recent advances regarding fundamental issues of geo-spatial information science (space and time, spatial analysis, uncertainty modeling and geo-visualization), and new scientific and technological research initiatives for geo-spatial information science (such as spatial data mining, mobile data modeling and location-based services), Advances in Geo-Spatial Information Science will be of interest for academics and professionals interested in spatial information science, spatial data handing and modeling of geographic systems"-- Provided by publisher.
"A Balkema book."
Keywords: Geographic information systems.; Geospatial data.; elektronické knihy; electronic books